Influence of the hatching strategy on consolidation during selective electron beam melting of Ti-6Al-4V - Scharowsky, Thorsten; Bauereiß, Andreas; Körner, Carolin (International Journal of Advanced Manufacturing Technology, 2017)
Selective electron beam melting is a promising powder-based additive manufacturing process offering a multitude of parameters to influence the melting process. In the presented work, the energy input, given by the beam power, scan speed, and hatch spacing, is investigated regarding their influence on the heat distribution, chemical composition, and surface roughness. Experiments and numerical simulations with the lattice Boltzmann method were performed to achieve a profound understanding. Process maps dependent on beam power and scan speed for different hatch spacings were developed. The influence of process parameters on the chemical composition, surface roughness, and heat-affected zone was investigated. The experimental results are explained with the help of numerical simulations by the temperature profile during hatching.
Keywords: Chemical composition; Hatching strategy; Selective electron beam melting; Ti-6Al-4V